Artificial Intelligence in the context of research ethics in education: academic and scientific integrity in crisis? (Práxis Educativa, 2025)
The purpose of this article was to reflect on the real conditions for considering the use of Artificial Intelligence (AI) in educational research, based on the following question: What ethical and integrity implications are present in academic and institutional contexts, whether in universities and/or research funding agencies? To highlight the current stage of the debate in educational research, publications on the subject produced in Brazil between 2023 and 2025 were selected, totaling five articles and one news piece. This made it possible to examine the reality of technology use and the responsibilities placed on Higher Education and graduate programs, both for institutions and for researcher training. The reflection revealed that the challenge faced by institutions and training processes regarding the use of AI does not keep pace with the speed of its development, which divides opinions: some argue that there is a crisis, marked by transformations, while others have embraced indiscriminate use without concern.Keywords: Crisis. Higher Education. Researcher education.